2008
DOI: 10.1021/bc800059t
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD22-MCC-DM1 and MC-MMAF Conjugates: Impact of Assay Format on Pharmacokinetic Parameters Determination

Abstract: CD22 represents a promising target for antibody-drug conjugate therapy in the context of B cell malignancies since it rapidly internalizes, importing specifically bound antibodies with it. To determine the pharmacokinetic parameters of anti-CD22-MCC-DM1 and MC-MMAF conjugates, various approaches to quantifying total and conjugated antibody were investigated. Although the total antibody assay formats gave similar results for both conjugates, the mouse pharmacokinetic profile for the anti-CD22-MCC-DM1 and MC-MMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…The effect is small, however, and the difference in clearance between total trastuzumab and T-DM1 was barely differentiated with a 7-day observation period (18). The results are not unique to T-DM1 as other Ab-SMCC-DM1 conjugates have similarly shown slightly faster clearance of conjugate versus total antibody in preclinical studies (11,21). The preclinical observations with T-DM1 appear to translate to the clinic: analysis of data from four clinical studies of single agent T-DM1 administered at 3.6 mg/kg every 3 weeks have shown that the clearance rate of T-DM1 and total trastuzumab in patients ranged from 7 to 13 and 3 to 6 mL/kg/day, respectively, with half-lives of about 4 and 9-11 days for T-DM1 and for total trastuzumab, respectively (13).…”
Section: Pharmacokineticsmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect is small, however, and the difference in clearance between total trastuzumab and T-DM1 was barely differentiated with a 7-day observation period (18). The results are not unique to T-DM1 as other Ab-SMCC-DM1 conjugates have similarly shown slightly faster clearance of conjugate versus total antibody in preclinical studies (11,21). The preclinical observations with T-DM1 appear to translate to the clinic: analysis of data from four clinical studies of single agent T-DM1 administered at 3.6 mg/kg every 3 weeks have shown that the clearance rate of T-DM1 and total trastuzumab in patients ranged from 7 to 13 and 3 to 6 mL/kg/day, respectively, with half-lives of about 4 and 9-11 days for T-DM1 and for total trastuzumab, respectively (13).…”
Section: Pharmacokineticsmentioning
confidence: 97%
“…The superior thioether stability of the Ab-SMCC-DM1 ADCs as compared to the cysteine linked ADCs may stem from inherent differences in the Michael donor reactivity of the sulfhydryl group of DM1 vs. the sulfhydryl group of cysteine side chains (25). Additional work is necessary to understand the mechanism(s) that underlie these pharmacokinetic observations (11,13,21). One might speculate that such maytansinoid loss may be accounted for by a low rate of cleavage of the amide bond of the linker-DM1 species from the antibody and/or by a slightly faster rate of clearance from circulation of species with more than the median load of DM1 molecules per antibody versus those species with less than the median number of DM1 molecules per antibody.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In addition to the discussion in the review articles [1][2][3] one well-accepted opinion is that the assay format, using different combination of capture and detection reagents, could affect the DAR characteristics of total-antibody and conjugated-antibody assays and hence the PK parameters [18,19]. Ideally, a DAR insensitive ADC conjugated-antibody assay is preferred [1][2][3]20].…”
Section: Ligand-binding Assays (Lba) For Adc Pkmentioning
confidence: 99%
“…Total anti-CD22 (hu10F4), anti-CD22 (hu10F4)-MCC-DM1 and free DM1 were analyzed as previously described. 16 All animals were euthanized and necropsied on either day 25 or 43 and tissues were thoroughly evaluated by gross and microscopic examination. Urinalysis was performed on urine collected by cystocentesis at necropsy.…”
Section: Cynomolgus Monkey Safety Studymentioning
confidence: 99%